STRATEGI PEMASARAN UMKM OLEH-OLEH MAKANAN KHAS PONTIANAK - Nurdin, Muhammad; Dolorosa, Eva; Oktoriana, Shenny (Universitas Sebelas Maret, 2023)
Pontianak City has typical food souvenirs to support its tourism industry but still has problems in marketing the product. This situation has been getting worse since pandemic covid-19. This research aims to determine a marketing strategy for Pontianak food souvenirs MSMEs to increase their income. The research method uses a descriptive method with a SWOT analysis tool to determine alternative strategies. Samples were 19 informants consisting of 4 key informants and 15 regular informants. The SWOT analysis results led to a WO (Weakness - Opportunity) Strategy with five alternative strategies. 1) Promoting products through Facebook Ads. 2) Expand the marketing area by selling in supermarkets and e-commerces. 3) Utilize the government grants for MSMEs that Covid-19 hurt to promote and keep product availability. 4) Registering and displaying products at the Pontianak UMKM Center also has to participate in the business skills improvement program. 5) Participate in exporting programs and increasing product quality according to foreign market standards.